2004
DOI: 10.1111/j.1651-2227.2004.tb03016.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased QT dispersion in breath‐holding spells

Abstract: QT dispersion is increased in patients with breath-holding spells, and this finding justifies further investigation for rhythm abnormalities and autonomic dysfunction in this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 23 publications
1
36
1
Order By: Relevance
“…Breath-holding spells usually occur in the breast-feeding period and disappear spontaneously before school age (Akalin et al, 2004). The youngest case in the literature is a 3-day-old infant with positive family history, whereas the oldest case involves a patient aged 11 years 8 months (Breukels et al, 2002;Low et al, 1955).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Breath-holding spells usually occur in the breast-feeding period and disappear spontaneously before school age (Akalin et al, 2004). The youngest case in the literature is a 3-day-old infant with positive family history, whereas the oldest case involves a patient aged 11 years 8 months (Breukels et al, 2002;Low et al, 1955).…”
Section: Discussionmentioning
confidence: 95%
“…The youngest case in the literature is a 3-day-old infant with positive family history, whereas the oldest case involves a patient aged 11 years 8 months (Breukels et al, 2002;Low et al, 1955). The attacks often occur with emotional stimuli or after minor trauma; they are characterized by endexpiratory respiratory arrest, color change in the skin, and a change or loss of consciousness or postural tone (Akalin et al, 2004;Guilleminault et al, 2007). Although the exact etiology is unknown, the most common suspected risk factor is iron deficiency, with or without anemia (Algarin et al, 2003;Kurekci et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, our results show that patients with cyanotic BHSs had an increased duration of bradycardia and arrhythmia after spells, despite the absence of a difference in ECG measures of ventricular repolarisation to those patients with pallid spells. Similarly, other studies found no difference in terms of ventricular repolarisation parameters between patients with cyanotic or pallid spells.…”
Section: Discussionmentioning
confidence: 71%
“…Electrocardiographic parameters were previously studied in children with BHS; however, there are no studies in the literature on p wave length and duration of PWD in these children (1,13).…”
Section: Discussionmentioning
confidence: 99%